Investigating Strategies and Best Practices in Teaching Heat and Temperature: a Systematic Review in Science and Physics Education - Riski Muliyani; Andi Suhandi; Eka Cahya Prima (Jurnal Penelitian Pendidikan IPA, 2023)
Teaching heat and temperature is a fundamental aspect of science and physics education. This systematic review investigates the strategies and best practices employed in science education and physics education to effectively teach heat and temperature concepts. A comprehensive search was conducted in reputable databases, resulting in the identification of relevant publications published between 2018 and 2023. Content analysis techniques were applied to analyze the selected publications, focusing on the techniques, outcomes, and conclusions presented. The review highlights a diverse range of instructional strategies, such as in-class demonstrations, virtual methods, and computer simulations, utilized to teach temperature and heat concepts. Educators are encouraged to consider these strategies to enhance student understanding. Furthermore, the review provides a valuable compilation of effective teaching practices, serving as a practical resource for educators and researchers in the field of temperature and heat education. Overall, the review emphasizes the necessity for further research on successful teaching approaches in temperature and heat education, offering valuable insights for both researchers and educators.